Child Care Costs and Mothers' Labor Supply: An Empirical Analysis for Germany - Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This study analyzes the effect of child care costs on the labor supply of mothers with preschool children in Germany using data from the German Socio-Economic Panel (2002). Child care costs are estimated on the basis of a sample selection model. A structural household utility model, which is embedded in a detailed tax-benefit microsimulation model, is used for labor supply estimation. In contrast to a previous German study, I find significant effects of child care costs on mother?s labor supply. Compared to other countries such as the US, Canada or the UK, the effects are rather small, which can be explained by the fact that child care costs are already heavily subsidized in Germany.
Keywords: J22; J13; 330; Child care costs; labor supply estimation; Kinderbetreuung; Kosten; Mütter; Frauenerwerbstätigkeit; Arbeitsangebot; Schätzung; Deutschland